International consensus guidance for management of myasthenia gravis: Executive summary. (26th July 2016) - Sanders, Donald B.; Wolfe, Gil I.; Benatar, Michael; Evoli, Amelia; Gilhus, Nils E.; Illa, Isabel; Kuntz, Nancy; Massey, Janice M.; Melms, Arthur; Murai, Hiroyuki; Nicolle, Michael; Palace, Jacqueline; et al.
Abstract : Objective: To develop formal consensus-based guidance for the management of myasthenia gravis (MG). Methods: In October 2013, the Myasthenia Gravis Foundation of America appointed a Task Force to develop treatment guidance for MG, and a panel of 15 international experts was convened. The RAND/UCLA appropriateness methodology was used to develop consensus guidance statements. Definitions were developed for goals of treatment, minimal manifestations, remission, ocular MG, impending crisis, crisis, and refractory MG. An in-person panel meeting then determined 7 treatment topics to be addressed. Initial guidance statements were developed from literature summaries. Three rounds of anonymous e-mail votes were used to attain consensus on guidance statements modified on the basis of panel input. Results: Guidance statements were developed for symptomatic and immunosuppressive treatments, IV immunoglobulin and plasma exchange, management of impending and manifest myasthenic crisis, thymectomy, juvenile MG, MG associated with antibodies to muscle-specific tyrosine kinase, and MG in pregnancy. Conclusion: This is an international formal consensus of MG experts intended to be a guide for clinicians caring for patients with MG worldwide.